PENGARUH PROSES PEMBELAJARAN PPKn TERHADAP LITERASI BUDAYA KEWARGAAN SISWA KELAS VIII SMPN 6 SIAK HULU - Mila Rosa Roslina; Hambali, Hambali; Arianto, Jumili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by problems related to students cultural and civic literacy, such as intolerant attitudes towards diversity among people in everyday life. Students sense of respect decreases and they tend to carry out intolerant and bullying actions such as bullying and discrimination. This research aims to find out whether there is an influence of the PPKn learning process on students' civic cultural literacy. The method in this research is descriptive quantitative, data analysis was carried out on the research sample using a statistical approach. The data collection instrument uses a questionnaire consisting of 30 questions. The population in this study was class VIII students at State Middle School 6 Siak Hulu (SMPN 6 Siak Hulu), totaling 195 students with a sample of 54 respondents. Based on the research results, it was found that there was a positive influence between the PPKn learning process on the civic cultural literacy of class VIII students at SMPN 6 Siak Hulu. This can be proven by a simple regression analysis test using the statistical test program SPSS version 23, so that the test results obtained are F count is 78.97 while F table is 4.02, so it can be concluded that in this case Fcount is greater than Ftable, then Ha accepted and H0 rejected. The influence of the PPKn learning process on civic cultural literacy is 77.7%. Meanwhile, 22.3% (100%-77.7%) was influenced by other variables not examined in this study.